LEGAL PROTECTION OF LAND RIGHTS ACQUIRED FROM MIXED MARRIAGES - Yanuar Ika Safitri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Mixed marital unions between Indonesian Citizens (WNI) and Foreign Nationals (WNA) may precipitate legal complexities, particularly concerning the governance of land title interests and the apportionment of inherited estates. Such complications arise due to the stipulations of Indonesian land law, which restrict the entitlement to Title Right (Hak Milik) solely to Indonesian citizens, as prescribed under Law Number 5 of 1966 concerning the Basic Agrarian Law (UUPA). This research seeks to examine the modalities of legal safeguards pertaining to land rights derived from mixed marriages, alongside the procedural frameworks for the distribution of hereditary land assets within such unions. Employing a normative legal methodology, this study adopts statutory and conceptual approaches, drawing upon primary, secondary, and tertiary legal sources subjected to descriptive analysis. The findings reveal that legal protection over land rights in mixed marriages may be realized through the execution of a prenuptial agreement stipulating the separation of marital assets, thereby enabling the Indonesian spouse to retain land under Title Right status. In matters of inheritance, foreign nationals are still recognized as heirs; however, ownership of land title rights is restricted by the obligation to release or transfer such rights within one year of acquisition, downgrade the right to right of use (hak pakai), or sell the land to a qualifying party in accordance with the applicable laws and regulations.